2021
DOI: 10.1177/01945998211064275
|View full text |Cite
|
Sign up to set email alerts
|

Corticosteroid Use in Otolaryngology: Current Considerations During the COVID‐19 Era

Abstract: Objective To offer pragmatic, evidence-informed advice on administering corticosteroids in otolaryngology during the coronavirus disease 2019 (COVID-19) pandemic, considering therapeutic efficacy, potential adverse effects, susceptibility to COVID-19, and potential effects on efficacy of vaccination against SARS-CoV-2, which causes COVID-19. Data Sources PubMed, Cochrane Library, EMBASE, CINAHL, and guideline databases. Review Methods Guideline search strategies, supplemented by database searches on sudden sen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 181 publications
(333 reference statements)
0
10
0
Order By: Relevance
“…Six of eight patients in the present study received systemic steroids in the acute phase of the disease. In retrosptect, this treatment must be re-evaluated critically regarding a potential attenuation of the vaccine-induced immune response against SARS-CoV-2 (12,75,76). When the patients presented with acute vestibular symptoms, they usually did not mention that they had received a recent COVID-19 vaccination, and the question about vaccination status was not part of our clinical routine before this study.…”
Section: Implications For Treatment and Further Covid-19 Vaccinationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Six of eight patients in the present study received systemic steroids in the acute phase of the disease. In retrosptect, this treatment must be re-evaluated critically regarding a potential attenuation of the vaccine-induced immune response against SARS-CoV-2 (12,75,76). When the patients presented with acute vestibular symptoms, they usually did not mention that they had received a recent COVID-19 vaccination, and the question about vaccination status was not part of our clinical routine before this study.…”
Section: Implications For Treatment and Further Covid-19 Vaccinationsmentioning
confidence: 99%
“…Consulting an immunologist or infectious disease specialist is useful in this context. As described for SSNHL after COVID-19 vaccinations before (9,12,75), intratympanic application of steroids into the affected ear is also an alternative (17).…”
Section: Implications For Treatment and Further Covid-19 Vaccinationsmentioning
confidence: 99%
“…The treatment of SSHL after COVID-19 vaccination is the same as in the absence of the vaccine. Good clinical practice guidelines indicated that corticosteroids can be administered within two weeks as initial therapy for SSHL [ 14 ]. Corticosteroids, immunosuppressive agents, or diseases of vaccine recipients can affect the antibody response to the vaccination.…”
Section: Resultsmentioning
confidence: 99%
“…Although this treatment protocol modifies the classic one (three administration in one week), our clinical experience in the treatment of post COVID-19 hearing loss supported us in using this therapy with good results. If a systemic high dose of steroid was administered during the vaccination period, a measurement of the antibody titer could be necessary after completion of the vaccination [ 14 ].…”
Section: Resultsmentioning
confidence: 99%
“…Systemic corticosteroid is recommended in patients with severe COVID-19 ( 37 ), and almost all patients with severe COVID-19 in this cohort were administered systemic corticosteroid. Although it is still unknown whether systemic steroid influences the stomal granulation ( 38 ), the lower rate of stomal granulation might be influenced by systemic corticosteroid. In addition, the decannulation rate was significantly lower in the control group.…”
Section: Discussionmentioning
confidence: 99%